Atomic structure of the entire mammalian mitochondrial complex I - Fiedorczuk, Karol (Nature, 2016)
Mitochondrial complex I plays a key role in cellular energy production by transferring electrons from NADH to ubiquinone coupled to proton translocation across the membrane1,2. It is the largest protein assembly of the respiratory chain with total mass of 970 kDa3. Here we present a nearly complete atomic structure of ovine mitochondrial complex I at 3.9 Å resolution, solved by cryo-electron microscopy aided by crosslinking/mass-spectrometry mapping. All 14 conserved core and 31 mitochondria-specific supernumerary subunits are resolved within the L-shaped molecule. The hydrophilic matrix arm harbours FMN and 8 iron-sulphur clusters involved in electron transfer, and the membrane arm contains 78 transmembrane helices, mostly contributed by antiporter-like subunits involved in proton translocation. Supernumerary subunits form an interlinked, stabilizing shell around the conserved core. Tightly bound lipids (including cardiolipins) further stabilize interactions between the hydrophobic subunits. Subunits with possible regulatory roles contain additional cofactors, NADPH and two phosphopantetheine molecules, revealed to be involved in inter-subunit interactions. We observe two different conformations of the complex, which may be related to the conformationally driven coupling mechanism and to the active/deactive transition of the enzyme. Our structure provides insight into complex I mechanism, assembly, maturation and dysfunction, allowing detailed molecular analysis of disease-causing mutations.